Locally Advanced Breast Implant-Associated Anaplastic Large-Cell Lymphoma: A Case Report of Successful Treatment with Radiation and Chemotherapy - Estes, Christopher F.; Zhang, Da; Reyes, Ruben; Korentager, Richard; McGinness, Marilee; Lominska, Christopher (Frontiers in Oncology, 2015)
The development of breast implant associated anaplastic large cell lymphoma (ALCL) is a rare phenomenon. A typical presentation is an effusion associated with a breast implant. Less commonly, disease can become more advanced locoregionally or distantly. The optimal treatment schema is a topic of debate: localized ALCL can potentially be cured with implant removal alone, while other cases in the literature, including those that are more advanced, have been treated with varying combinations of surgery, chemotherapy, and external beam radiotherapy. This is a case report of breast implant ALCL with pathologically proven lymph node involvement, the fifth such patient reported. Our patient experienced a favorable outcome with radiation therapy and chemotherapy.